Penerapan Metode Wafa Untuk Meningkatkan Kemampuan Membaca Al-Qur’an di SDIT Tawakkal Pacitan - Reti Maita Safriani; Mokhamad Choirul Hudha (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research article was conducted to determine the effectiveness of the application of the wafa method, namely a method using the right brain in improving the ability to read the Al-Qur'an at SDIT Tawakkal Pacitan for the 2023/2024 academic year. This wafa method has been implemented at SDIT Tawakkal since 2018, making it the first elementary school in Pacitan to apply the Wafa method for learning the Al-Qur'an. This research was carried out from 25 May 2024 to 25 June 2024. This research was carried out at SDIT Tawakkal involving students in class 3 B or Ali Bin Abi Talib class as research subjects. The research uses descriptive methods with a qualitative approach. Based on research in the field, it was found that the application of the wafa method at SDIT Tawakkal can improve the ability to read the Al-Qur'an.